Implications of Land Sale and Purchase Agreements with Unconverted Eigendom Rights - Ginting, Yuni Priskila (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
Legal developments have shown that the absence of evidence of conversion of former Eigendom land can be a basis for canceling the land sale and purchase agreement. In general, to decide that a sale and purchase agreement for ex-eigendom land is null and void, the court must consider the evidence presented by the parties involved in the trial. Research involving a case approach and legislation plays an important role in determining whether a sale and purchase agreement for ex-eigendom land can be considered valid or null and void. If there is not sufficient evidence to show that the Eigendom land has been converted into legal ownership, then the court has the authority to declare that the sale and purchase agreement is invalid. The court's decision in this case is based on legal principles governing evidence and evidence in court. If during the trial there is no sufficient evidence to show that the eigendom land has been converted, then the court can decide by the law to protect the interests of the parties involved in the land transaction. This shows the importance of ensuring that all requirements and procedures stipulated in the law are fulfilled in every land transaction to avoid disputes and legal problems in the future.